2020
DOI: 10.1111/acer.14497
|View full text |Cite
|
Sign up to set email alerts
|

Intoxication Effects on Impulsive Alcohol Choice in Heavy Drinkers: Correlation With Sensation Seeking and Differential Effects by Commodity

Abstract: Background The preference for immediate rewards and high sensation seeking are both potent risk factors for alcohol use disorder (AUD), but how they interact during intoxication is poorly understood. To model decision making linked to AUD risk, we tested heavy drinkers for impulsive choice (delay discounting with alcohol:money or money:money) and behavioral sensation seeking using a novel odor choice task. Laboratory tasks measured actual behavior with real contingencies. Our goals were to determine, in heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
(95 reference statements)
2
4
0
Order By: Relevance
“…However, monetary choices appear to be a reasonable proxy for reward decision making for other commodities, as cross-commodity alcohol: money choices are strongly correlated with single-commodity monetary discounting, even while intoxicated (Oberlin et al, 2021), consistent with prior work suggesting a common underlying preference that underlies temporal discounting of many commodities (Odum, 2011).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, monetary choices appear to be a reasonable proxy for reward decision making for other commodities, as cross-commodity alcohol: money choices are strongly correlated with single-commodity monetary discounting, even while intoxicated (Oberlin et al, 2021), consistent with prior work suggesting a common underlying preference that underlies temporal discounting of many commodities (Odum, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…Although DD tasks using monetary reinforcers have a strong record in detecting group differences between those with addictions and healthy controls, single‐commodity monetary DD does not precisely model alcohol‐specific AUD decision making (involving the choice between intoxication and other future rewards). However, monetary choices appear to be a reasonable proxy for reward decision making for other commodities, as cross‐commodity alcohol: money choices are strongly correlated with single‐commodity monetary discounting, even while intoxicated (Oberlin et al, 2021), consistent with prior work suggesting a common underlying preference that underlies temporal discounting of many commodities (Odum, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…Viewed as a psychobiological personality trait, sensation‐seeking incorporates an individual’s desire for novelty, intensity, and complexity in their experiences (Arnett, 1994; Roberti, 2004). High sensation‐seeking is a well‐known predictor for increased alcohol use and hazardous drinking (Hirvelä, Sipilä, & Keski‐Rahkonen, 2022; Hittner & Swickert, 2006; Lac & Donaldson, 2021; Oberlin et al., 2021; Sznitman & Engel‐Yeger, 2017; Yanovitzky, 2006). Thus, it could be suggested that the ‘value for money' mentality is employed to achieve/experience the maximum sensation of intoxication effects.…”
Section: Discussionmentioning
confidence: 99%
“…The ACT quantifies sensation seeking behavior as the relative preference for a mild, safe odorant ‘Standard’ versus a more intense, novel, and variable option that may be aversive ‘Varied’ ( Oberlin et al., 2020 ). The manual sniff bottle version ( Oberlin et al., 2021 ) was used in the present study. The number of “Varied” choices selected divided by the total (40) yields the choice ratio, which ranges from 0 to 1, with larger values indicating a greater degree of behavioral sensation seeking.…”
Section: Methodsmentioning
confidence: 99%
“…Four additional control trials (magnitude discrimination) were randomly included to ensure attentive responding. To counter the strategy of avoiding alcohol choices to hasten release, subjects were instructed that they may not leave before 5:30PM ( Oberlin et al., 2021 ). We titrated delay to avoid fractional—and potentially unintuitive—units of ‘One Shot’ for the immediate reward ( Locey et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%